The importance of proper evidence and identification of metallurgical materials for effective management of the company - Schindlerová Vladimíra; Šajdlerová Ivana (MATEC Web of Conferences, 2018)
An important characteristic for efficient management of production systems is the ability of a product, component or material to be tracked. That is, to be assigned with a unique symbol, number, or other code (identifier) that can be traced back both within the production process and to the customer (e. g. when complaining about a defective part). Traceability leads to a cost reduction in eliminating the risks associated with the difficult identification of the material or parts, their handling in pre-production, the manufacturing process, or the storage and sale of finished products to customers. In case of problems, it makes it easier to implement the necessary measures and reduces the time to remedy the situation either within the company or even outside. Individual companies within the Czech Republic usually solve the identification and traceability independently. The paper deals with the results of the analysis of the current state of record keeping and identification of metallurgical materials in selected companies, and presents a proposal for improvement of the current situation in a specific company, especially in the field of work with remaining material.